(untitled) (Eurasian Journal of Religious Studies, 2024)
The article provides an overview of research on religious identity conducted by the scholars from Kazakhstan. An analysis of various methodological approaches and the evolution of the study of religious identity in Kazakhstan was carried out. The findings were obtained through application of a qualitative analysis of 21 publications using the keyword “Religious identity” in two internationally recognized citation databases, i.e., “Scopus” and “Web of Science”. Through application of such research method, the authors attempted to answer the research questions relating to following issues; the aspects religious scholars from Kazakhstan pay attention to and scientific conclusions they reached when studying the problem of religious identity, the hierarchy of factors influencing the formation of religious identity, interaction of religious identity with other spheres of identity and forms of its manifestation. The analysis of publications allowed the authors to carry out some terminological differentiation and identify the main priority areas that would enable scholars from Kazakhstan to formulate future research tasks. Further, the article focuses specifically on the religious identity of women and provides the results of the analysis of educational, age, ethnic, and cultural factors forming and changing their religious identities. At the same time, the analysis of the selected publications made it possible to identify the gaps jeopardizing the advancement of the scholarship of religious identity in Kazakhstan. Key words: religious identity, religious values, globalization, society, trust, view.